Evaluation of liquefaction potential in reworked volcanic-colluvial deposits of the Bawen Area, Semarang Regency - Vidayanti, Desiana; Ramli Nazir; Ratnaningsih, Ratnaningsih; Komerdevi, Det; Simatupang , Pintor Tua; Fitriani, Eka Nur (Teknisia, 2025)
Liquefaction is a major geotechnical hazard that can severely damage infrastructure in earthquake-prone areas. This study evaluates the liquefaction potential of volcanic–colluvial deposits in Semarang Regency, Central Java, using Standard Penetration Test (SPT) data and the Simplified Procedure of Seed and Idriss (1971). Cyclic Stress Ratio (CSR) and Cyclic Resistance Ratio (CRR) were computed to obtain Factors of Safety (FS) under three earthquake scenarios (Mw = 5.0, 5.9, and 6.5). Results show that for Mw = 6.5, the shallow sandy layers at 0-3 m have FS = 0.07-0.21 (highly susceptible), while the 4.5-9 m interval is FS = 0.8-0.96 (marginal to near-threshold) and and the >10 m strata remain stable (FS > 1.2). For Mw = 5.9, shallow liquefaction is confined to 0-3 m (FS = 0.09-0.27), with the 4.5-9 m zone showing FS = 1.0-1.2 (marginal to stable). Even for Mw = 5.0, the 0-3 m layer yields FS = 0.14-0.41, indicating liquefaction susceptibility, whereas deeper layers are stable (FS > 1.0-1.2). These findings indicate that loose, saturated silty-sand layers with shallow perched groundwater are the most critical to cyclic softening. The site is underlain by reworked volcanic-colluvial materials derived from Mount Ungaran, characterized by fine-grained, near-saturated deposits within the upper 10 m. Compared with previous studies in northern Semarang, this study highlights the moderate liquefaction susceptibility of southern volcanic-colluvial terrains, an area rarely analyzed in Central Java and provides practical insights for toll-road foundation design and mitigation strategies in similar geological settings.